Achieving a balance in the execution of the will between the testator, the beneficiary, and the heir: a case study of Amanah Raya Berhad (ARB) - Azziz, Raouane; Ruhi Fadzlyana Jailani; Sahid, Mualimin Mochammad (Penerbit Universiti Kebangsaan Malaysia, 2023)
The arrival of Islam ensured balance in all its legislation. The property owner has the right of implementing the will and protecting the rights of the heirs, whereby a balance is achieved between the owner and those entitled to the property inheritance. Islam allows the property owner the right to dispose of a third of his ownership by will for whomever he wished during his life and the remaining property belongs to the heirs is not valid to be dispose of. This right is God’s commandment that enjoined the inheritance to those who deserve it according to the shares determined by the Sharia. Herein lies the research problem; the Shariah did not give freedom to the property owner to do as he wish to. Rather, Islam specified the recommended amount which he should not exceed. The aim of this study is to discuss and analyze the case of will writing in Amanah Raya Berhad (ARB), and the conditions for its implementation. This study relied on inductive approach, by following the opinions of the jurists and their evidence regarding the conditions of entitlement to the will and the validity of its contract for the benefactor. An analytical method is used in discussing and analyzing the opinions and evidence of the jurists to the provisions with what is done in the Amanah Raya Berhad (ARB). This study reached important results: Amanah Raya Berhad (ARB) did not acknowledge the obligatory bequest (wasiat wajibah) if the owner of the property did not make a will. This contrasts with the Fatwa Department in Malaysia. Amanah Raya Berhad (ARB) prohibits the will of the heir and suspended its implementation on the consent of the heirs. It permitted a non-Muslim to make a will and freedom to carry out his will.